Tendency of using chemical, biological, radiological and nuclear weapons for terrorist purposes - Krstić, Marko M. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Chemical, biological, radiological and nuclear (CBRN) terrorism is a serious problem, and its threat and use lead to a new era of terrorism: the epoch much more dangerous than any of the previous periods and the terrorism no one yet knows how to cope with. The disturbing fact is that terrorists can come into possession of weapons of mass destruction. Therefore, the goal of the paper is to analyze the probability of CBRN terrorist actions which have highlighted the growing concerns and increasing signs of convergence between terrorism and CBRN unconventional weapons for terrorist purposes. Terrorism today includes technologies available to anyone and anywhere and deployed through innovative solutions where it is also necessary to understand a complex interaction between the dynamic behavior of terrorist groups and the decisions regarding old and new technologies. The prospect of the use of CBRN terrorism has been confirmed by many countries as an acute security challenge that requires an efficient and quick response and reaction. The paper will also explain the importance of understanding the relationship between terrorist groups and non-conventional weapons, as well as difficulties in identifying factors that may cause the escalation. Since the end of 1990s and since the tragedy of September 11, 2001 in particular, government officials of many countries have pointed out the possibility that terrorist organizations eventually can come into the possession of unconventional materials and develop the possibilities of their use against some countries.